Corneal stromal lenticule transplantation for the treatment of corneal ulcers - Yun Min Klimesova; Martina Nemcokova; Magdalena Netukova; Alina-Dana Baxant; Marcela Hlavackova; Jana Kacerovska; Pavel Studeny (Biomedical Papers, 2024)
Purpose. To evaluate the safety and efficacy of using corneal stromal lenticules (CSLs) obtained during refractive surgery Refractive Lenticule Extraction (ReLEx) with the Small Incision Lenticule Extraction (SMILE) procedure for the treatment of corneal ulcers. Methods. This retrospective study included 12 eyes of 12 patients, 7 men and 5 women with varying degrees of corneal ulcer. The mean age was 64 ± 18 (range 34 to 95 years). The monitoring included corrected distance visual acuity (CDVA), slit-lamp biomicroscopy examination, a Seidel test, stability of the graft and anterior segment optical coherence tomography (AS-OCT) inspection. Patients were closely monitored for possible postoperative complications for at least 6 months. Results. In 7/12 (58%) eyes, the corneal ulcer was successfully sealed with CSL and amniotic membrane (AM) without the need for any additional surgical intervention. In 3 eyes, penetrating keratoplasty (PK) was needed in addition to CSL transplantation and in 2 eyes the scleral patch was used to fully seal after CSL transplantation. During the follow-up period no signs of rejection or infection were detected in any patient. Conclusion. The use of CSLs from ReLEx SMILE may be considered as an alternative method for the treatment of corneal ulcers before a more extensive and definitive solution - PK - is used. Our preliminary findings suggest that properly performed CSL transplantation using cryopreserved lenticules is a safe and effective method to temporarily cover the corneal partial-thickness defect or even perforation.